Gender Role Attitude with an Emphasis on Ethnicity and Gender - Leila Falahati (Taḥqīqāt-i Farhangī-i Īrān, 2016)
Gender roles defined as the patterns of behavior which are approved by society and culture. In other words gender role is the way men and women doing to recognition as feminine and masculine and culture, and society accepted and encourage those behaviors as appropriate behavior for men and women. Present study aimed to study gender role attitude using Islamic gender role attitude scale. A sample of 400 male and female students at public universities including Allameh-Tabataba'i University, Tehran University and the University of Kurdistan was drawn. Respondents were selected using random sampling method and data were collected with questionnaire. Results revealed that there were no traditional gender role attitude among students and all the respondents have professional and liberal attitude toward gender roles. There were significant gender differences between male and female in gender role attitude so that female students have more liberal attitude. In terms of ethnicity there were gender differences in Fars and Lur attitude, so that male have professional and female have liberal attitude. Among Kurdish respondents, male and female have liberal attitude while among Turkish, both male and female have traditional-professional attitude.